Oligocene benthic foraminifera from the Paleogene Wenonah Canyon, Scotian Shelf – normal versus canyon assemblages - Thomas, Francis (Atlantic Geology, 2005)
ABSTRACT Petro-Canada Shell Wenonah J-75 well was drilled at the site of the mid Cenozoic "Wenonah Canyon" under the Scotian Shelf. Benthic foraminiferal assemblages recovered from sidewall core samples in the Oligocene section are unusually low in species diversity, though high in numbers of specimens. Such oligospeciﬁc assemblages may be the result of unusual hydrological factors in the canyon sediments at the time of deposition. In marked contrast, a nearby well, Canterra et al. Whycocomagh N-90, drilled outside the deepest canyon area, contains normal, more diverse, benthic slope assemblages. A seismic section acquired near the Wenonah site shows the informally designated Ypresian Acadia chalk to be truncated by canyon development. Planktic foraminifera of early Ypresian age do occur in Wenonah J-75, however, suggesting that the Acadia chalk may in fact be conﬁned to the upper Ypresian.